Troponins, Acute Coronary Syndrome and Renal Disease: From Acute Kidney Injury Through End-stage Kidney Disease - Debasish Banerjee (Radcliffe Medical Media, 2019)
The diagnosis of acute coronary syndromes (ACS) is heavily dependent on cardiac biomarker assays, particularly cardiac troponins. ACS, particularly non-ST segment elevation MI, are more common in patients with acute kidney injury, chronic kidney disease (CKD) and end-stage kidney disease (ESKD), are associated with worse outcomes than in patients without kidney disease and are often difficult to diagnose and treat. Hence, early accurate diagnosis of ACS in kidney disease patients is important using easily available tools, such as cardiac troponins. However, the diagnostic reliability of cardiac troponins has been suboptimal in patients with kidney disease due to possible decreased clearance of troponin with acute and chronic kidney impairment and low levels of troponin secretion due to concomitant cardiac muscle injury related to left ventricular hypertrophy, inflammation and fibrosis. This article reviews the metabolism and utility of cardiac biomarkers in patients with acute and chronic kidney diseases. Cardiac troponins are small peptides that accumulate in both acute and chronic kidney diseases due to impaired excretion. Hence, troponin concentrations rise and fall with acute kidney injury and its recovery, limiting their use in the diagnosis of ACS. Troponin concentrations are chronically elevated in CKD and ESKD, are associated with poor prognosis and decrease the sensitivity and specificity for diagnosis of ACS. Yet, the evidence indicates that the use of high-sensitivity troponins can confirm or exclude a diagnosis of ACS in the emergency room in a significant proportion of kidney disease patients; those patients in whom the results are equivocal may need longer in-hospital assessment.